2005
DOI: 10.1038/nri1733
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and macrophage heterogeneity

Abstract: Heterogeneity of the macrophage lineage has long been recognized and, in part, is a result of the specialization of tissue macrophages in particular microenvironments. Circulating monocytes give rise to mature macrophages and are also heterogeneous themselves, although the physiological relevance of this is not completely understood. However, as we discuss here, recent studies have shown that monocyte heterogeneity is conserved in humans and mice, allowing dissection of its functional relevance: the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

86
4,032
6
79

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 4,489 publications
(4,203 citation statements)
references
References 90 publications
86
4,032
6
79
Order By: Relevance
“…However, there is accumulating evidence that neutrophils are the first wave of leukocytes that pave the way for the succeeding monocytes, which eventually differentiate into macrophages and dendritic cells. 18 Interestingly, we observed that the meninges covering the ischemic area seem to be the exclusive point of entry for the aforementioned first wave of leukocytes. Mast cells residing in the meninges have been discussed as important factor for the early influx of neutrophils, 19,20 which in turn attracted monocytes by releasing 'find me' and 'eat me' signals.…”
Section: Discussionmentioning
confidence: 72%
“…However, there is accumulating evidence that neutrophils are the first wave of leukocytes that pave the way for the succeeding monocytes, which eventually differentiate into macrophages and dendritic cells. 18 Interestingly, we observed that the meninges covering the ischemic area seem to be the exclusive point of entry for the aforementioned first wave of leukocytes. Mast cells residing in the meninges have been discussed as important factor for the early influx of neutrophils, 19,20 which in turn attracted monocytes by releasing 'find me' and 'eat me' signals.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, the Ly6C low subsets lack Ccr2 but express high levels of Cx3cr1. The expression of Ccr2 and the capacity to migrate toward the Ccr2 ligand CC‐chemokine ligand 2 (CCL2) is consistent with the role of this chemokine and its receptor in the recruitment of monocytes to inflammatory lesions, so the subset of monocytes that expresses Ccr2 is known as the ‘inflammatory’ subset (Gordon and Taylor, 2005). Within inflamed tissues, Ccr2 + Cx3cr1 low Ly6C + monocytes differentiate into macrophages (blood‐derived macrophages).…”
Section: Introductionmentioning
confidence: 76%
“…Within inflamed tissues, Ccr2 + Cx3cr1 low Ly6C + monocytes differentiate into macrophages (blood‐derived macrophages). In the absence of inflammation, Ccr2 ‐ Cx3cr1 hi Ly6C ‐ monocytes are postulated to enter the tissues and replenish the ‘tissue‐resident’ macrophage, known as resident microglia in the brain (Gordon and Taylor, 2005). To distinguish resident microglia from blood‐derived macrophages in the brain after injury, Saederup et al generated red fluorescent protein (RFP)‐Ccr2 knock‐in mice (Ccr2 RFP/RFP ) and crossed them with green fluorescent protein (GFP)‐Cx3cr1 mice (Cx3cr1 GFP/GFP ) (Saederup et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They also fulfill homeostatic functions including tissue remodeling and the resolution of tissue damage. Heterogeneity of the macrophage lineage has long been recognized (Gordon & Taylor, 2005), and they have different functional roles depending on their tissue location and the inflammatory environment that drives their activation (Davies et al ., 2013). In this context, macrophage activation has been conventionally categorized into pro‐inflammatory M1 macrophages, induced by IFN‐γ and toll‐like receptor (TLR) ligands, and the alternatively activated anti‐inflammatory M2 macrophages, induced by IL‐4/IL‐13 (Biswas & Mantovani, 2010; Gordon & Martinez, 2010).…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%